The nerve growth factor-responsive PC12 cell line does not express the Myc dimerization partner Max. - Hopewell, R (1995)
Heterodimerization of Max with the nuclear oncoprotein Myc and the differentiation-associated proteins Mad and Mxi1 enables these factors to bind E-box sites in DNA and control genes implicated in cell proliferation and differentiation. We show that in the PC12 pheochromocytoma tumor cell line, functional Max protein is not expressed because of the synthesis of a mutant max transcript. This transcript encodes a protein incapable of homo- or heterodimerization. Furthermore, the mutant Max protein, unlike wild-type Max, is incapable of repressing transcription from an E-box element. Synthesis of mutant max transcripts appears to be due to a homozygous chromosomal alteration within the max gene. Reintroduction of max into PC12 cells results in repression of E-box-dependent transcription and a reduction in growth rate, which may explain the loss of Max expression either during the growth of the pheochromocytoma or in subsequent passage of the PC12 cell line in vitro. Finally, the ability of these cells to divide, differentiate, and apoptose in the absence of Max demonstrates for the first time that these processes can occur via Max- and possibly Myc-independent mechanisms.